2022
DOI: 10.1371/journal.pgph.0000124
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of kidney function among people living with HIV initiating antiretroviral therapy in Zambia

Abstract: As the response to the HIV epidemic in sub-Saharan Africa continues to mature, a growing number of people living with HIV (PLHIV) are aging and risk for non-communicable diseases increases. Routine laboratory tests of serum creatinine have been conducted to assess HIV treatment (ART) suitability. Here we utilize those measures to assess kidney function impairment among those initiating ART. Identification of non-communicable disease (NCD) risks among those in HIV care creates opportunity to improve public heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(47 reference statements)
0
0
0
Order By: Relevance
“…The result presented in table 3 shows a significant increase (P = 0.003) in creatinine level and also increase in urea level though not statistical significant (P = 0.085). This finding in table 3 is in line with previous studies by [2,26] showing the ameliorative effect of HAART on the kidney of those subjects placed on HAART.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result presented in table 3 shows a significant increase (P = 0.003) in creatinine level and also increase in urea level though not statistical significant (P = 0.085). This finding in table 3 is in line with previous studies by [2,26] showing the ameliorative effect of HAART on the kidney of those subjects placed on HAART.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were in line with the work by Scialla et al [25] who correlated viral load, decreasing CD4 cells count and occurrence of renal failure and stated that administration of HAART suppresses viral load and returns renal function to normal at a close proximity. Again a previous study in Zambia [26] reported that individuals living with HIV on HAART had better kidney function when compared to HIV positive HAART naïve subjects.…”
Section: Discussionmentioning
confidence: 93%